A hybrid paretosearch algorithm and goal attainment method for maximizing production and reducing blast-induced ground vibration: a blast design parameter selection approach. Issue 3 (2nd July 2020) - Arthur, Clement Kweku; Kaunda, Rennie B.
ABSTRACT: This study uses a hybrid paretosearch algorithm and goal attainment method to determine blast design parameters that will maximize production (total blasted volume) and minimize blast-induced ground vibration. Fifty-five (51) blast data collected at Quarry X in the Western US are used. A nonlinear and linear regression models are developed to serve as the objective function for the minimization of blast-induced ground vibration and maximization of production respectively. The blast design parameters are then determined using the hybrid optimization technique. The results obtained show that hole depths of 11.58 m, burden of 4.24 m, spacing of 4.88 m and stemming length of 3.61 m are the blast design parameter values that produce a minimum PPV within the interval of 0.51 and 38.1 mm/sec as stated in the Explosive regulation by the Colorado State Division of Oil and Public Safety for a total blast volume greater than 16, 622 m 3 .